Strategies to improve reproductive outcomes after empty follicle syndrome: a case report - Tomaizeh, Aida (2022)
Empty follicle syndrome (EFS) is the complete failure to retrieve oocytes after ovarian stimulation, despite apparently normal follicular development and adequate follicular steroidogenesis. Two variants of EFS have been described: the genuine form, which occurs in the presence of adequate circulating bhCG or LH levels at the time of oocyte aspiration, and the 'false' form, which is associated with serum hCG/LH levels below a critical threshold. In our patient, after an accepted protocol of ovarian stimulation with human menopausal gonadotropin and follitropin alfa and subsequent follicular maturation with choriogonadotropin alfa, no oocyte clusters were obtained in the ultrasound-guided puncture, so an attempt was made to use other strategies aimed at correcting this situation. The treatment and prognosis of these patients are still poorly understood. Large multicenter studies and systematic reviews are needed to increase understanding of EFS and thus its management, designing better strategies as we tried to do with our patient with the use of double discharge for oocyte maturation.